AN EVALUATION OF HUMAN RESOURCE ACCOUNTING ON CORPORATE PERFORMANCE - Jimoh, A. L.; Salman, A.; Yahaya, I. J. (Farabi Journal of Social Sciences, 2023)
The accounting component of human capital has not yet been fully adopted and implemented in corporate financial reporting of corporate organizations. Determining the impact of human resource accounting on turnover, earnings per share, and capital employed of corporate performance of the listed businesses in the Nigerian stock exchange is the goal of the current study. The study used a descriptive longitudinal research design, and the sample size used was 29, with the study population being made up of 188 companies that are listed on the Nigerian Stock Exchange. The study employed both descriptive and inferential statistical tools of analysis. The inferential statistical approach used was panel regression analysis, and frequency tables were the descriptive approach for the study's demography part. The results of the study demonstrate that (I) human resource accounting significantly influences business turnover, (ii) human resource accounting significantly influences earnings per share, and (iii) human resource accounting significantly influences return on capital employed. In conclusion, the financial reports would be more useful for making decisions if human resources were included as an asset rather than reported in the traditional manner. Therefore, the study suggests that the listed firms adopt a culture of valuing and disclosing education, training, and ongoing retraining of their human resources to enhance performance. Key words: Human resource accounting, turnover, earnings per share, return on capital employed, education and training.